Physical Characteristics of Cocoa Butter and Palm Stearin Mixture in Milk Chocolate System - Misnawi Jati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2008)
Chocolate products for consumption in tropical areas frequently become soft and tend to bloom due to melting and migration of fat contained, the product becomes dully and less interesting. Fat fraction determines chocolate texture, appearance and its handling. Objective of this research is to study the characteristic of mixed fat of cocoa butter, milk fat and stearin; in which the latest was added into a chocolate formula expected to increase its physical characteristic. Response Surface Methodology design was used for the study at stearin concentration of 10–60 g kg-1 and lecithin of 1–7 g kg-1. Parameters of the study were fat melting point, chocolate hardness and preference on chocolate texture and overall acceptance. Result of the study showed that the stearin concentration significantly altered chocolate physical characteristic, where the lecithin concentration did not influence. The presence of stearin in milk chocolate system showed fat eutectic phenomenon. Substitution of cocoa butter with stearin up to concentration of 35 g kg-1 in the formulation showed a clear eutectic; however, at higher concentrations the phenomenon was compensated by the increase in stearin crystal seed which raised melting point and hardness. This result also clearly indicated that cocoa butter substitution with palm stearin to obtain resistant chocolate should be designed in a range of 43–60 g kg-1 in its formulation, equal to 15–18% from cocoa butter added.Key words : chocolate, cocoa butter, stearin, eutectic, solidifier, emulsifier, melting point, texture.